Endeavouring to Grasp the Elusive: A New Study of Finnboga saga ramma - Martina Ceolin (Gripla, 2024)
Finnboga saga ramma, ‘The Saga of Finnbogi the Mighty’, is a fourteenth-century Íslendingasaga that tracks the restless life of Finnbogi Ásbjarnarson, an Icelandic chieftain’s son, as it unfolds in tenth-century Iceland, Norway, and Byzantium. The narrative is compelling for several reasons, including how it challenges the commonly acknowledged taxonomy of saga genres, clearly combining elements that pertain to the repertoires of different saga genres. Moreover, the two main codices preserving the text, Möðruvallabók (AM 132 fol., 14th century) and Tómasarbók (AM 510 4to, mid-16th century), present it in two very different contexts, making its study from the perspective of genre even more significant. This contribution investigates Finnboga saga ramma from the genre perspective by giving equal consideration to the architecture of the text itself and the two main manuscript contexts in which it appears, in order to shed light on both the generic characteristics of the text and on the significance of studying ‘late’ Íslendingasögur – and medieval sagas generally – from within their material contexts.